InFish: A Professional Network to Promote Global Conservation and Responsible Use of Inland Fish. Issue 6 (14th April 2020) - Lynch, Abigail J.; Bartley, Devin M.; Beard, Thomas Douglas; Bunnell, David B.; Cooke, Steven J.; Cowx, Ian G.; Funge‐Smith, Simon; Paukert, Craig P.; Rogers, Mark W.; Taylor, William W.
Abstract : Inland fishes and fisheries make substantial contributions to individuals, society, and the environment in a changing global landscape that includes climate, water allocations, and societal changes. However, current limitations to valuing the services provided by inland fish and their fisheries often leaves them out of key decision‐making discussions. InFish is a voluntary professional network with over 120 members from over 50 organizations in over 20 countries that seeks to address challenges facing inland fish through novel approaches and international collaborations. InFish fosters opportunities to share knowledge, pursue proposals, publications, and conference‐related events focused on inland fisheries. InFish has become a source of inland fisheries expertise, working collectively towards global conservation and sustainable use of inland fish through informing scientifically sound management practices. As such, InFish may serve as a model network for other natural resource challenges now and into the future.